Prenatal exposure to a mixture of organophosphate ester and organophosphorus pesticides in relation to child neurodevelopment in the Shanghai Birth Cohort - Hui Wang; Dezheng Fu; Xiaoning Liu; Xiaochen Chang; Siyu Guo; Xiaomeng Cheng; Ying Tian; Jinjun Ran; Jun Zhang; Shengju Yin (Ecotoxicology and Environmental Safety)
Neurotoxicity of organophosphate esters (OPEs) and organophosphorus pesticides (OPPs) has been documented in toxicological studies, though epidemiological evidence remains inconsistent. The developing fetal brain is susceptible to environmental exposures. Thus, we aim to investigate how prenatal exposure to OPEs and OPPs as mixture affects offspring neurodevelopment in preschool-aged children. In a study involving 530 mother-child dyads from the Shanghai Birth Cohort (SBC) with enrollment occurring between 2013 and 2016, 14 OPEs/OPPs metabolites were evaluated using high-performance liquid chromatography/tandem mass spectrometry (HPLC/MS-MS) in maternal urine collected during both the first and second trimester. Child neurodevelopment was evaluated using the parent-reported Behavior Rating Inventory of Executive Function-Preschool version (BRIEF-P) and the Strengths and Difficulties Questionnaire (SDQ). We utilized multivariable linear regression and Bayesian kernel machine regression (BKMR) to estimate associations with individual and mixture component, respectively. We also investigated whether these associations varied by child sex. Of the 14 OPEs/OPPs metabolites, 6 were quantifiable in over 75 % of the samples. Higher prenatal O,O-dimethyl phosphate (DMP) concentrations in the first and second trimesters, as well as O,O-dimethyl thiophosphate (DMTP) in the second trimester, were associated with more behavioral difficulties. When stratified by child sex, the statistically significant inverse associations were observed exclusively in girls. Results from BKMR showed that the overall effect of prenatal exposure to OPEs and OPPs mixtures was associated with some neurodevelopmental domains in girls. For example, holding the mixture at the 75th percentile compared to the 50th percentile during the first trimester was associated with a 0.65 increase in SDQ total scores (95 % confidence interval: 0.03–1.26). DMP and DMTP may be the dominant contributors. Our findings add to the literature on the effect of prenatal exposure to OPEs and OPPs on offspring neurodevelopment and suggest that the effect seems to be sex-specific. Additional research is required to validate our findings and elucidate the underlying mechanisms.